Political-Economic Comparison of The World Bank and The New Development Bank - Widjanarko, Yeremia Nicolaus (Jurnal Ilmu Ekonomi Terapan, 2024)
Although stated as one of the influential actors in international relations and discussed in many previous studies, MDB had yet to be comprehensively depicted. Through this research, the author intended to fill this gap by comparing the World Bank as a traditional MDB and the New Development Bank as a Neo MDB within the international economic order. By comparing the political and economic anatomy such as ownership structure, distribution of voting power in decision-making, establishment objectives, types of financing services, operational coverage, sources of funding, private sector options, and service customization and examining them using an organizational political-economy approach, the author found both MDBs had significant differences in carrying out their functions as cross-border financial institutions.